DAYA MELARUTKAN EKSTRAK AKAR AREN (Arenga pinnata (Wurmb.) Merr.) TERHADAP BATU GINJAL KALSIUM IN VITRO - Sofwan haris (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2019)
Palm sugar (Arenga pinnata (Wurmb.) Merr.) is a plant belonging to the familyPalmae that functions as traditionalmedicine. The root of sugar palm containssaponins, flavonoids, and polyphenols,flavonoids which allegedly has the power todissolve calcium kidney stones. The purposeof this study to prove the ability dissolving rootsugar palm extracts to calcium kidney stonesand to determine the optimal concentration ofroot sugar palm extracts that can dissolvecalcium kidney stones. This research included trueexperimental research. Palm sugar roots wereextracted by maceration method usingmethanol: water (1:1), obtained extract wascondensed and then made a series of levels,namely: 9%, 18%, 27%, 32%, 45%,(v/v). Then from a series of levels is used tosoak of calcium kidney stones for ±5 hours at37 0C with suffle every hour. Results ofimmersion measured turbidity withTurbidimeter. Turbidity values used tocalculate the dissolved calcium content usingstandard curves of calcium oxalate. Dissolvedcalcium concentration data was then tested byone way Anova 95% confidence level. Result showed that the root extractpalm sugar with levels of 9%, 18%, 27%, 32%,45% (v/v) has the capacity to dissolve calciumkidney stones. Optimal levels of palm rootextract that can dissolve calcium kidneystones is 32% v/v. Results of statisticalanalysis using one-way anova with 95%confidence level showed no significantdifferences from each levels of root palmsugar extracts (significance <0.005).